Response of Soil Microbial Community to Vegetation Reconstruction Modes in Mining Areas of the Loess Plateau, China - Zhao, Jiao; Ma, Jing; Yang, Yongjun; Yu, Haochen; Zhang, Shaoliang; Chen, Fu (Frontiers in Microbiology, 2021)
Vegetation reconstruction and restoration is vital to the health of the mine land ecosystem. Different vegetations usually control the colonization and assembling of soil microbes in roots, mediating the biogeochemical cycle and nutrition supply to the soil. To clarify the response of soil microbes to different vegetation reconstruction modes in the mining areas of the Loess Plateau, China, soil bacterial and fungal community structures and functions, as well as key environmental factors were determined by the MiSeq high throughput sequencing combined with PICRUSt2 and FUNGuild tools. The fungal community richness was observed to be the highest in grassland soil and positively correlated with soil organic matter, total nitrogen, and nitrate nitrogen. The bacterial and fungal community structures were similar in grassland and brushland areas, but were significantly differentiated in the coniferous and broadleaf forest, and the leading factors were soil pH and nitrate nitrogen. Different vegetation reconstruction modes did not affect the bacterial functional communities but shaped different functional groups of fungi. The grassland soil was dominated by saprotrophic fungi, while symbiotroph fungi dominated the coniferous and broadleaf forests. These findings improve the understanding of microbial ecology in the reclaimed mine soil and provide a reference for the ecological restoration of fragile mining ecosystems.